O papel da mulher no design digital : uma investigação a partir da trajetória feminina dos anos 1970 - Brêtas, Flavia de Araújo (2022)
This dissertation brings an analysis of the role of women in digital design based on an investigation of the female trajectory of the 1970s. It briefly presents who were some of the most notorious pioneers in computing and digital design in the West, the cradle of the digital revolution. It also mentions the context in which the first important works done by women in digital design took place. The text also features a brief review of feminism and its relationship with the insertion of women in the labor market up to the present day, highlighting its relevance so that we currently have a large proportion of women in Brazilian Digital Design, according to the data shown in this work. Finally, the work brings two surveys on the professional landscape faced by women in Brazilian digital design today, where the comparative analyzes carried out based on data obtained in previous editions of the Panorama UX survey stands out.